Analisis Faktor yang Mempengaruhi Keputusan Penggunaan Bank Digital di Kalangan Mahasiswa POLBAN - Elis Nisa Amalia (International Journal Administration, Business & Organization, 2023)
The purpose of this research is to find out the factors that influence the decisions of POLBAN students in using digital banks. This research was conducted at the Bandung State Polytechnic with 121 respondents from engineering and non-engineering majors. Data was collected through a questionnaire. Data analysis was carried out using the factor analysis method to find out what factors influence the decision to use digital banks among POLBAN students. The results of this study are that the decision to use digital banks among POLBAN students is at least influenced by three factors, namely reputation and security factors, convenience factors, and social factors.